Identification of novel drug targets and small molecule discovery for MRSA infections - Subramani, Nandha Kumar; Venugopal, Subhashree (Frontiers in Bioinformatics, 2025)
IntroductionThe topmost deadliest microorganism, namely, methicillin-resistant Staphylococcus aureus (MRSA), causes dreadful infections like bacteremia, pneumonia, endocarditis, and systemic inflammations. The virulence factors associated with MRSA exhibit multidrug-resistant characteristics, complicating treatment choices. So, the primary objective of this study is to identify the MRSA virulence factors and inhibiting its activity utilizing bioinformatic approaches.MethodsThe screening of novel therapeutic MRSA targets was conducted based on the predictions retrieved from non-homologous, physicochemical analysis, subcellular localization, druggability, and virulence factor examinations. Following that, flavonoid compounds were docked against specific MRSA targets using AutoDock Vina. Further, molecular dynamic simulations and binding free energy calculations were performed using simulation software.ResultsAfter examining 2,640 virulence factors that presented in MRSA, the heme response regulator R (HssR) was found to be a novel protein that greatly controls the levels of heme in MRSA infections. Subsequently, the binding energy calculations for flavonoid compounds and HssR revealed that the catechin provided −7.9 kcal/mol, which surpassed the standard drug, namely, vancomycin (−5.9 kcal/mol). Further, the results were validated by evaluating molecular dynamic simulation parameters like RMSD, RMSF, ROG, SASA, and PCA. Through analyzing these parameters, catechin provided a more stable, compact nature and less solvent exposure with HssR than vancomycin. Moreover, the predicted binding free energy for HssR-catechin was found to be −23.0 kcal/mol, which was less compared to the HssR-vancomycin (−16.91 kcal/mol) complex. The results suggested that the catechin was able to modulate the activity of the HssR protein effectively.ConclusionThese potential findings revealed that heme response regulator R as a promising therapeutic target while the flavonoid compound catechin could act as alternative therapeutic inhibitor that target MRSA infections.